2020
DOI: 10.1038/s41375-020-0732-1
|View full text |Cite
|
Sign up to set email alerts
|

SRSF1 mediates cytokine-induced impaired imatinib sensitivity in chronic myeloid leukemia

Abstract: Patients with chronic myeloid leukemia (CML) who are treated with tyrosine kinase inhibitors (TKIs) experience significant heterogeneity regarding depth and speed of responses. Factors intrinsic and extrinsic to CML cells contribute to response heterogeneity and TKI-resistance. Among extrinsic factors, cytokine-mediated TKI-resistance has been demonstrated in CML progenitors, but the underlying mechanisms remain obscure. Using RNA-sequencing, we identified differentially expressed splicing factors in primary C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…RNA-Seq raw data are accessible at NCBI Gene Expression Omnibus with the accession number GSE129547. More data were downloaded from the NCBI Sequence Read Archive (SRA) with the accession numbers GSE140385 (CD34 + hematopoietic stem cells [43]), GSE142831 (adipose-derived mesenchymal stem cells) and GSE81827 (cardiosphere-derived cells [44]). Here, we took care to select datasets of paired end sequencing runs from the Illumina platform to minimize technical variability between the groups.…”
Section: Rna-seq and Bioinformatic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…RNA-Seq raw data are accessible at NCBI Gene Expression Omnibus with the accession number GSE129547. More data were downloaded from the NCBI Sequence Read Archive (SRA) with the accession numbers GSE140385 (CD34 + hematopoietic stem cells [43]), GSE142831 (adipose-derived mesenchymal stem cells) and GSE81827 (cardiosphere-derived cells [44]). Here, we took care to select datasets of paired end sequencing runs from the Illumina platform to minimize technical variability between the groups.…”
Section: Rna-seq and Bioinformatic Analysismentioning
confidence: 99%
“…Here, we took care to select datasets of paired end sequencing runs from the Illumina platform to minimize technical variability between the groups. In detail, we accessed expression data of cardiosphere-derived cells (CDC) [44], CD34+ hematopoietic stem cells (HSC) [43] and adipose-derived mesenchymal stem cells (AdMSC) (NCBI GEO-accession number GSE142831). From these studies, we selected the datasets of the control groups, to use only expression data of untreated cells.…”
Section: Hcscs and Itscs Share Higher Similarities In Gene Expression Profiles With Admscs And Cdcs Than With Hscsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, plasmacytoid dendritic cells (pDC), the major producers of IFN-α in vivo, promoted nilotinib resistance in CML patients (33). These studies imply that the cytokines released by immune cells in BM microenvironment, and the transcriptomic changes they bring about on the LSCs, may activate cytokinedependent TKI resistance programmes (34). Together, these single-cell studies demonstrate that GE signatures within malignant and non-malignant compartments in CML are prognostically informative.…”
Section: Single-cell-based Ge Analysismentioning
confidence: 98%
“…Several recent studies have correlated splicing patterns with disease outcome to demonstrate that particular splicing events have prognostic value with regard to survival and disease progression (Tian et al 2019;Anande et al 2020;Xie et al 2020). Even more excitingly, two studies have demonstrated a correlation between expression of RBPs and/or specific splicing patterns in leukemia, with sensitivity to specific chemotherapeutics (Sciarrillo et al 2020;Sinnakannu et al 2020). If validated in broader studies, the potential for alternative splicing analysis, either alone or coupled with gene expression, to differentiate responders from nonresponders of various therapies, would be of tremendous value in guiding effective personalized medicine approaches in cancer treatment.…”
Section: Leveraging Alternative Splicing To Improve Cancer Therapymentioning
confidence: 99%